Identification of three Asian otter species (Aonyx cinereus, Lutra sumatrana, and Lutrogale perspicillata) using a novel noninvasive PCR-RFLP analysis - Sharm, Sandeep; Woo, Chee Yoong *; Adrian, Kannan; Rao, Suganiya Rama; Pazil, Abdul-Patah; Shyamala, Ratnayeke * (Wiley Open Access, 2022)
Four species of otters occur in tropical Asia, and all face multiple threats to their survival. Studies of distribution and population trends of these otter species in Asia, where they occur sympatrically, are complicated by their elusive nature and difficulties with reliable identification of species in field surveys. In Malaysia, only three species, the smooth-coated otter, Asian small-clawed otter, and hairy-nosed otter have been reliably reported as residents. We designed a replicable and cost-efficient PCR-RFLP protocol to identify these three species. Using published reference sequences of mitochondrial regions, we designed and tested three PCR-RFLP protocols on DNA extracted from reference samples and 33 spraints of wild otters collected along the North Central Selangor Coast of Malaysia. We amplified and sequenced two fragments (450 and 200 bp) of the mt D-loop region and a 300-bp fragment of the mt ND4 gene using primer sets TanaD, TanaD-Mod, and OTR-ND4, respectively. Amplification products were digested with restriction enzymes to generate species-specific RFLP profiles. We analyzed the costs of all three protocols and compared these with the costs of sequencing for species identification. Amplification success was highest for the smallest PCR product, with the TanaD-Mod primer amplifying DNA from all 33 spraints. TanaD and OTR-ND4 primers amplified DNA from 60.6% and 63.6% spraints, respectively. PCR products of TanaD-Mod provided the expected species-specific RFLP profile for 32 (97%) of the spraints. PCR products of OTR-ND4 provided the expected RFLP profile for all 21 samples that amplified, but TanaD produced spurious bands and inconsistent RFLP profiles. The OTR-ND4 primer–enzyme protocol was the least expensive (437 USD) for processing 100 samples, followed by TanaD-Mod (455 USD). We suggest the use of both OTR-ND4 and TanaD-Mod protocols that show potential for highly efficient and reliable species identification from noninvasive genetic sampling of three Asian otter species. We expect our novel noninvasive PCR-RFLP analysis methods to facilitate population monitoring, ecological and behavioral studies on otters in tropical and subtropical Asia.